Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Panda, Sayantan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Molecular Biology, 2017)
Alternaria solani severely affects tomato (Solanum lycopersicum L.) yield causing early blight (EB) disease in tropical environment. Wild relative, Solanum arcanum Peralta could be a potential source of EB resistance; however, its underlying molecular mechanism largely remains unexplored. Hence, non-targeted metabolomics was applied on resistant and susceptible S. arcanum accessions upon A. solani inoculation to unravel metabolic dynamics during different stages of disease progression. Total 2047 potential metabolite peaks (mass signals) were detected of which 681 and 684 metabolites revealed significant modulation and clear differentiation in resistant and susceptible accessions, respectively. Majority of the EB-triggered metabolic changes were active from steroidal glycol-alkaloid (SGA), lignin and flavonoid biosynthetic pathways. Further, biochemical and gene expression analyses of key enzymes from these pathways positively correlated with phenotypic variation in the S. arcanum accessions indicating their potential role in EB. Additionally, transcription factors regulating lignin biosynthesis were also up-regulated in resistant plants and electrophoretic mobility shift assay revealed sequence-specific binding of rSaWRKY1 with MYB20 promoter. Moreover, transcript accumulation of key genes from phenylpropanoid and SGA pathways along with WRKY and MYB in WRKY1 transgenic tomato lines supported above findings. Overall, this study highlights vital roles of SGAs as phytoalexins and phenylpropanoids along with lignin accumulation unrevealing possible mechanistic basis of EB resistance in wild tomato.

WRKY1 acts as a key component improving resistance against Alternaria solani in wild tomato, Solanum arcanum Peralta - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Biotechnology Journal, 2018)
Early blight (EB), caused by Alternaria solani, is a major threat to global tomato production. In comparison with cultivated tomato (Solanum lycopersicum), a wild relative, S.arcanum exhibits strong resistance against EB. However, molecular cascades operating during EB resistance in wild or cultivated tomato plants are largely obscure. Here, we provide novel insight into spatio-temporal molecular events in S.arcanum against A.solani. Transcriptome and co-expression analysis presented 33-WRKYs as promising candidates of which 12 SaWRKYs displayed differential expression patterns in resistant and susceptible accessions during EB disease progression. Among these, SaWRKY1 exhibited induced expression with significant modulation in xyloglucan endotrans hydrolase 5 (XTH5) and MYB2 expressions that correlated with the disease phenotypes. Electro-mobility shift assay confirmed physical interaction of recombinant SaWRKY1 to SaXTH5 and SaMYB2 promoters. Comparative WRKY1 promoter analysis between resistant and susceptible plants revealed the presence of crucial motifs for defence mechanism exclusively in resistant accession. Additionally, many defence-related genes displayed significant expression variations in both the accessions. Further, WRKY1 overexpressing transgenic plants exhibited higher levels of EB resistance while RNAi silencing lines had increased susceptibility to A.solani with altered expression of XTH5 and MYB2. Overall, these findings demonstrate the positive influence of WRKY1 in improving EB resistance in wild tomato and this could be further utilized as a potential target through genetic engineering to augment protection against A.solani in crop plants.
Keywords: Alternaria solani; early blight; Solanum arcanum; Tomato; WRKY1; XTH5

High-throughput metabolomic and transcriptomic analyses vet the potential route of cerpegin biosynthesis in two varieties of Ceropegia bulbosa Roxb. - Gharat, Sachin A.; Shinde, Balkrishna A.; Mule, Ravindra D.; Punekar, Sachin A.; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Ramaswamy, Gopalakrishna; Giri, Ashok P. (Planta, 2020)
Ceropegia bulbosa is an important medicinal plant, used in the treatment of various ailments including diarrhea, dysentery, and syphilis. This is primarily attributed to the presence of pharmaceutically active secondary metabolites, especially cerpegin. As this plant belongs to an endemic threatened category, genomic resources are not available hampering exploration on the molecular basis of cerpegin accumulation till now. Therefore, we undertook high-throughput metabolomic and transcriptomic analyses using different tissues from two varieties namely, C. bulbosa var. bulbosa and C. bulbosa var. lushii. Metabolomic analysis revealed spatial and differential accumulation of various metabolites. We chemically synthesized and characterized the cerpegin and its derivatives by liquid chromatography tandem-mass spectrometry (LC-MS/MS). Importantly, these comparisons suggested the presence of cerpegin and 5-allyl cerpegin in all C. bulbosa tissues. Further, de novo transcriptome analysis indicated the presence of significant transcripts for secondary metabolic pathways through the Kyoto encyclopedia of genes and genomes database. Tissue-specific profiling of transcripts and metabolites showed a significant correlation, suggesting the intricate mechanism of cerpegin biosynthesis. The expression of potential candidate genes from the proposed cerpegin biosynthetic pathway was further validated by qRT-PCR and NanoString nCounter. Overall, our findings propose a potential route of cerpegin biosynthesis. Identified transcripts and metabolites have built a foundation as new molecular resources that could facilitate future research on biosynthesis, regulation, and engineering of cerpegin or other important metabolites in such non-model plants.
Keywords: 5-Allyl cerpegin; Ceropegia; Cerpegin; LC-MS; metabolite; Transcriptome

Characterized constituents of insect herbivore oral secretions and their influence on the regulation of plant defenses - Kallure, Gopal S.; Kumari, Archana; Shinde, Balkrishna A.; Giri, Ashok P. (Phytochemistry, 2022)
For more than 350 million years, there have been ongoing dynamic interactions between plants and insects. In several cases, insects cause-specific feeding damage with ensuing herbivore-associated molecular patterns that invoke characteristic defense responses. During feeding on plant tissue, insects release oral secretions (OSs) containing a repertoire of molecules affecting plant defense (effectors). Some of these OS components might elicit a defense response to combat insect attacks (elicitors), while some might curb the plant defenses (suppressors). Few reports suggest that the synthesis and function of OS components might depend on the host plant and associated microorganisms. We review these intricate plant-insect interactions, during which there is a continuous exchange of molecules between plants and feeding insects along with the associated microorganisms. We further provide a list of commonly identified inducible plant produced defensive molecules released upon insect attack as well as in response to OS treatments of the plants. Thus, we describe how plants specialized and defense-related metabolism is modulated at innumerable phases by OS during plant-insect interactions. A molecular understanding of these complex interactions will provide a means to design eco-friendly crop protection strategies.
Keywords: Effector; Elicitor; Herbivore insects; Oral secretion; Plant defense; Suppressor

Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense. - Kallure, Gopal S.; Shinde, Balkrishna A.; Barvkar, Vitthal T.; Kumari, Archana; Giri, Ashok P. (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores' oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenyl-propanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose

Diversity assessment of Gloriosa superba accessions from Western Ghats of India based on morphological traits, ISSR markers and metabolite content - Mahajan, Yogesh A.; Shinde, Balkrishna A.; Mulani, Fayaj A.; Gade, Akshay B.; Kasodekar, Amol K.; Thulasiram, H. V.; Kadoo, Narendra Y.; Nikam, Tukaram D. (Journal of Applied Research on Medicinal and Aromatic Plants, 2022)
Gloriosa superba L. (glory lily) is a medicinally and horticulturally important plant used as a commercial source of the alkaloid colchicine. The Western Ghats in India is mostly unexplored for the morphological, genetic, and metabolite diversity of the species. In the current study, three methodologies were employed to assess the diversity among 50 established accessions of G. superba collected from several locations in the Western Ghats. The morphological analysis revealed that, among the studied traits, seed yield per vine and dry seed weight per 100 seeds for the established accessions were the most diverse traits. The former exhibited a significantly positive correlation with four vegetative and five yield traits. The first three principal components showed nine traits contributing to the variation. Intra-specific molecular variation based on inter simple sequence repeat markers distributed the accessions in three clusters with high polymorphism and low genetic diversity indices. Liquid chromatography high-resolution mass spectrometry analysis revealed significant variation among the screened accessions for colchicine content in tuber and seed tissue. Interestingly, an unexplored tissue, pod shell, was found to contain significantly high colchicine, which could be explored for commercial colchicine extraction. The morphogenetic and metabolite variation revealed by the study would be useful to develop elite varieties to expand the cultivation of glory lily across the country, fulfilling the increasing demand for colchicine and providing remunerative income to the farmers.
Keywords: Colchicine; Genetic diversity; Gloriosa superba; Metabolite diversity; Morphological diversity; Western Ghats

Unlocking the genetic and biotechnological potential of Gloriosa superba to enhance its alkaloid production - Mahajan, Yogesh A.; Shinde, Balkrishna A.; Shirke, Harshad A.; Gandra, Jawahar; Suravajhala, Prashanth; Kishor, P. B. Kavi; Kadoo, Narendra Y.; Nikam, Tukaram D. (Industrial Crops and Products, 2024)
Gloriosa superba is a medicinally important plant that produces the pharmaceutically precious colchicine molecule. Colchicine is being used for treating gout, for enhancing the production of interleukin-8 (inhibits human pancreatic cancer) and many other human ailments. Since its seeds and rhizomes (tuberous roots) are the chief sources of colchicine, pharmaceutical industries exploit the natural sources, thus demolishing its habitat. Chemo- and genetic diversity among the G. superba populations exist, but has not been exploited profitably. Scope exists for generating mutants using the chemical mutagens and also via breeding methods to generate superior varieties for commercial cultivation. Innovative methods for breaking seed dormancy and superior colchicine extraction, besides biotechnological interventions are imperative to save the biodiversity and to produce colchicine on a large scale. Biorhizomes produced in vitro hold great promise for biomanufacturing colchicine in bioreactors commercially. Since the biosynthetic pathway of colchicine is now known, isolation of the pathway genes and their heterologous overexpression or the application of synthetic biology methods needs to be explored in future for industrial manufacturing of colchicine. Advances made in the recent past in these fields of colchicine production from G. superba are critically evaluated in this review.
Keywords: Biosynthetic pathway; Colchicine; Genetic diversity; Glory lily; Metabolite elicitation; Omics approaches

Transcriptome analyses reveal TaWRKY41 as a potential candidate governing spot blotch resistance in wheat - Dayama, Bhakti R.; Mahadik, Varsha A.; Somani, Deepika; Shinde, Balkrishna A.; Kondhare, Kirtikumar R.; Karthikeyan, Muthukumarasamy; Kadoo, Narendra Y. (Physiology and Molecular Biology of Plants, 2025)
Spot blotch disease caused by Bipolaris sorokiniana poses a significant threat to wheat production. Cultivation of disease-resistant wheat genotypes appears to be the most practical approach to mitigate the impact of this devastating disease. However, the molecular responses of wheat plants during spot blotch disease progression remain poorly understood. This study employed RNA-sequencing to unravel the spatiotemporal molecular events underlying the resistance mechanism in the spot blotch susceptible and resistant wheat genotypes. This study further provides a comprehensive overview of differentially expressed transcripts through functional analysis and transcription factor identification, elucidating the biological mechanisms governing wheat-B. sorokiniana interaction. In the resistant genotype, the expression of one of the key transcription factors, TaWRKY41, was significantly induced upon pathogen inoculation. Computational studies, electrophoretic-mobility shift assay, and yeast one-hybrid assay confirmed the interaction of the recombinant TaWRKY41 protein with W-box elements present in the promoters of plant defense-related genes. Furthermore, co-expression network analyses identified downstream genes positively correlated with TaWRKY41, providing insights into their probable involvement in the defense response. Overall, our investigation suggests that TaWRKY41 contributes to spot blotch resistance in wheat. This knowledge can help develop new disease-resistant wheat varieties.
Keywords: Plant defense; plant-pathogen interaction; TaWRKY41; Transcription factors; Transcriptomics